The Impact of Covid-19 Pandemic on The Work Landscape and Employment Policy Responses: Insights From Labor Policies Adopted in The Greek Context - Triantafillidou, Eleni; Koutroukis, Theodore (European Scientific Journal, ESJ, 2021)
This study explores the impact of Covid-19 on labor relations and public labor relations policies. Focus is given to the worldwide effects of the pandemic on employment, the impact of Covid-19 on the European labor landscape, the impact of the pandemic on the Greek labor context, and the main labor policies and measures adopted in Greece during Covid-19. The analysis of the effects of the pandemic on employment is based on published research material from ILO, Eurofound and the database of the Greek Ministry of Labor. The section concerning the impact of Covid-19 on the labor relations policies and the measures adopted in the Greek context is based on the analysis of the Greek institutional framework and the related legislative acts. The main employment policy responses to Covid-19 pandemic are ensuring workers’ safety, maintaining adequate paid sick leave, upholding support for workers with caring needs, adapting job retention schemes, ensuring adequate income protection, expanding employment services and training and giving the young people the support they need. Planning and implementing effective labor policies is a demanding goal that requires cooperation and synergies among economic, research, innovation and lifelong education policies.